PENGARUH PROGRAM UPAYA KHUSUS TERHADAP PRODUKTIVITAS, BIAYA POKOK PRODUKSI DAN PENDAPATAN USAHATANI KEDELAI DI KABUPATEN LAMPUNG TIMUR - Fajar Setya Dharma; Agus Hudoyo; Achdiansyah Soelaiman (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2021)
This study aims to analyze the impact of the Upsus program on those three variables. The sample of this study were chosen by the simple random sampling method. The total respondents were 66 farmers of soybean from two districts in three villages for each district. They were interviewed for their farm budget in dry season2014 for non-upsus and dry season 2018 for Upsus. Therefore, the total observations were 132. There are three dependent variables, i.e. yield, production standard cost (HPP), and profit. The independent variables were Upsus and location as a control variable. Data were analyzed by the multiple linear regression model. The results of this study revealed that the Upsus program had statiscally significant (α= 1%) impact on increasing the yield, decreasing the production standard cost, and increasing the profit of the soybean farming. Its yield increased 16%, i.e. from 1.35 ton/ha to 1.57 ton/ha. Its production standard cost decreased 19%, i.e. from IDR4.690/kg to IDR3,820/kg.  Its profit increased 57%, i.e. from IDR3.21 million/ha to IDR5.05 million/ha.Key words: cost, production, profit, soybean, yield